Dampak Pemanasan Global Terhadap Kesejahteraan Ternak Dan Produktifitas Di Kawasan Perdesaan - Syafrianti, Des; Zega, Asokhiwa (Jurnal Ilmu Peternakan Indonesia, 2024)
Global warming is increasingly becoming a significant threat to livestock welfare and productivity in rural areas, which rely heavily on the livestock sector for food security and income. This study aims to analyze the impacts of climate change on livestock productivity and evaluate adaptation strategies implemented by farmers in rural areas. The methods used include qualitative and quantitative approaches through surveys, in-depth interviews, and direct observation of farmers in climate change vulnerable areas. Data were analyzed using descriptive analysis and inferential statistics. The results showed that increased temperature and rainfall uncertainty had a negative impact on livestock health, feed availability and productivity. Adaptation strategies implemented by farmers, such as livestock species diversification and more efficient feed management, have helped mitigate some of the negative impacts, but limited access to technology and resources is a significant constraint in improving adaptive capacity. In addition, extension support and climate information are still limited, especially in remote areas. The discussion underscores the need for a holistic approach involving technical, social and policy aspects in supporting farmers' adaptation to climate change. Greater support from the government and relevant institutions is needed to improve farmers' access to information, technology and financing. In conclusion, the impacts of global warming on the livestock sector in rural areas are significant, and effective adaptation requires cross-sectoral support to ensure the sustainability of livestock productivity.